2000
DOI: 10.1161/01.cir.101.20.2368
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Reperfusion by Intravenous Myocardial Contrast Echocardiography and Coronary Flow Reserve After Primary Percutaneous Transluminal Coronary Angiography in Patients With Acute Myocardial Infarction

Abstract: Intravenous MCE can be used to define perfusion defects after AMI. Assessment of microcirculation by MCE corresponds to evaluation by CFR. Serial intravenous MCE has the potential to identify patients likely to have improved left ventricular function after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
124
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(128 citation statements)
references
References 33 publications
0
124
2
2
Order By: Relevance
“…This finding conflicts with other reports that used intracoronary Doppler ultrasound during myocardial infarction. 21,22 Lepper et al 21 found a CFR of Ն1.6 even in the infarct-related artery immediately after successful primary percutaneous coronary intervention, followed by good reperfusion as assessed by myocardial contrast echocardiography. Neumann et al 22 obtained a similar CFR (1.56 Ϯ 0.51) in the infarctrelated artery after primary percutaneous coronary intervention, which increased to 2.04 Ϯ 0.65 at 1 hour and to 2.66 Ϯ 0.72 at 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This finding conflicts with other reports that used intracoronary Doppler ultrasound during myocardial infarction. 21,22 Lepper et al 21 found a CFR of Ն1.6 even in the infarct-related artery immediately after successful primary percutaneous coronary intervention, followed by good reperfusion as assessed by myocardial contrast echocardiography. Neumann et al 22 obtained a similar CFR (1.56 Ϯ 0.51) in the infarctrelated artery after primary percutaneous coronary intervention, which increased to 2.04 Ϯ 0.65 at 1 hour and to 2.66 Ϯ 0.72 at 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…MCE has been proven to be an excellent method for the detection of microvascular dysfunction following angioplasty during infarction and for predicting subsequent recovery of function (6,8,9,12,13). TIMI grade 2 flow may be a less accurate indicator of ineffective perfusion than myocardial contrast perfusion (49); a recent study (50) suggested that MCE is superior to other modalities for assessing myocardial reperfusion after infarction.…”
Section: Previous Studiesmentioning
confidence: 99%
“…MCE can be used to reliably assess myocardial reperfusion following primary percutaneous coronary intervention (PCI) for AMI and to predict improvement in left ventricular (LV) function, as well as to assess the degree of collateral support to the infarcted territory (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) OBJECTIVES: To determine whether myocardial contrast echocardiography (MCE) can quickly and accurately assess myocardial perfusion and infarct-related artery (IRA) patency before emergency angiography during acute myocardial infarction (AMI). BACKGROUND: Despite encouraging experimental and clinical studies, the reliability and practicality of MCE in predicting IRA patency during AMI before angiography has not been proven.…”
mentioning
confidence: 99%
“…Recently, Lepper and his colleagues [29] investigated whether the extent of perfusion defects detected by intravenous MCE in patients with AMI treated by primary PTCA related to coronary flow reserve for assessment of myocardial reperfusion and was predictive for left ventricular recovery. Twenty-five patients with AMI underwent MCE with intermittent harmonic imaging before PTCA and after 24 hours.…”
Section: Assessment Of Myocardial Viability In Acute St Elevation Myomentioning
confidence: 99%